Alcohol consumption, genetic susceptibility, and risk of latent autoimmune diabetes in adults and type 2 diabetes : Findings from two population-based studies - Lampousi, Anna Maria; Ahlqvist, Emma; Alfredsson, Lars; Edstorp, Jessica; Di Giuseppe, Daniela; Grill, Valdemar; Löfvenborg, Josefin E.; Padyukov, Leonid; Tuomi, Tiinamaija ; 0000-0002-8306-6202; Åsvold, Bjørn O.; Carlsson, Sofia (Clinical Nutrition, 2025)
Background & aims: Alcohol consumption has been inversely associated with type 2 diabetes (T2D), but its influence on autoimmune diabetes is unclear. We investigated the risk of latent autoimmune diabetes in adults (LADA) and T2D in relation to alcohol intake and assessed if potential associations were modified by genetic susceptibility to diabetes. Methods: We used data from a case–control study with incident diabetes cases (n = 695 LADA and n = 2679 T2D) and matched controls (n = 2752), and a prospective cohort study with 59,710 participants and incident diabetes cases (n = 221 LADA and n = 3335 T2D). Pooled relative risks (RR) with 95 % confidence intervals (CI) were estimated in relation to self-reported alcohol consumption. Analyses were stratified according to human leukocyte antigen (HLA) genotypes and polygenic score (PGS) for T2D (T2D-PGS). Results: Moderate alcohol consumption (10–14.9 g/day) compared to low consumption (0.1–4.9 g/day) was associated with a reduced risk of LADA (RR: 0.74, CI: 0.56, 0.98) and T2D (RR: 0.81, CI: 0.69, 0.94). No further risk reduction was observed for the highest intake category (≥15 g/day). Stratification by T2D-PGS revealed an inverse association with LADA in those with high T2D-PGS (≥10 g/day vs. 0.1–4.9 g/day; RR: 0.38, CI: 0.23, 0.64), but not low/intermediate T2D-PGS (RR: 0.89, CI: 0.54, 1.46). The corresponding RRs for high- and low/intermediate-risk HLA carriers were 0.64 (CI: 0.35, 1.17) and 0.48 (CI: 0.31, 0.74). For T2D, RRs were 0.70 (95 % CI: 0.53, 0.93) in individuals with low/intermediate T2D-PGS and 0.85 (95 % CI: 0.64, 1.14) in those with high T2D-PGS. Conclusion: Moderate alcohol intake was linked to reduced LADA risk, particularly in individuals with high T2D-PGS and low/intermediate-risk HLA genotypes, indicating that the association is primarily present for T2D-like LADA. The extent to which genetic predisposition influences the association between alcohol and T2D remains less clear.
Publisher Copyright: © 2025 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license. http://creativecommons.org/licenses/by/4.0/
Keywords: Alcohol; Genetic susceptibility; Latent autoimmune diabetes in adults; Type 2 diabetes